Economic and Statistical Analysis of Stock Market Performance in Lebanon - Agabekova, N. V.; Abdo, A. N. A. (Statistics of Ukraine, 2021)
Analysis of financial processes is an important and fast developing branch of statistics. Statistical analysis is a combined analysis. Statistical methodology refers to a system of techniques and methods aimed at studying quantitative patterns in the dynamics and relationships of socio-economic phenomena. The main feature of the statistical methodology is also the specificity of research, expressed in the inextricable connection of quantitative analysis with the establishment of a qualitative uniqueness of objects in the concrete historical conditions of place and time. The use of the techniques of mathematical statistics and other branches of mathematics (applied, in particular) becomes a technical means of implementation. Lebanese stock market today is inactive and is shrinking. Historically, Lebanon had a relatively vibrant capital market in the Middle East before the stock exchange was closed for twenty years due to the civil war (1975-1995). Since its reopening in 1996, the stock market has been contracting. The establishment of Solidere in late 1990s and the renaissance of commercial banks energized the stock market for a while before the volatility of the market hold back. The article analyzed the change in the main indicators of the Lebanese stock market for the period from 2012 to 2019. The study developed a statistical model for the decomposition of time series, which was led to identify the trend, seasonal, cyclical and random components.. The simulation results made it possible to establish the patterns of changes in the share prices of the three leading enterprises representing the construction, industrial and banking sectors of the Lebanese economy. The length and depth of short-period cycles in the studied indicators time series were measured. It was found that the depth of cyclical fluctuations increases with decreasing stock prices of Lebanon’s construction and industrial enterprises under the influence of both economic and political processes, while the cyclic recurrence of stock prices in the banking sector was less pronounced and was mainly determined by changes in the economy